2008
DOI: 10.1536/ihj.49.459
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Systolic and Isolated Diastolic Dysfunction Sado Heart Failure Study

Abstract: SUMMARYDetermining the type of cardiac dysfunction is important for implementing therapeutic strategies and for prognostic insights. We characterized systolic dysfunction (SD) and isolated diastolic dysfunction (IDD) in adults referred for echocardiographic evaluation, and compared their clinical and other characteristics. In the present work, we studied 218 patients (137 males) with cardiac dysfunction (mean age, 66.3 ± 8.3 years). SD was defined as a left ventricular ejection fraction (LVEF) of < 45%, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Patients with HFpEF are older, more often female, and more frequently have hypertension compared to patients with HFrEF [2,11,12,[16][17][18][19][20][21]. Similar background differences were demonstrated in Japanese HF patients in both inpatient-based and community-based cohorts [3,4]. The differences in patients' backgrounds in our study were almost identical to those of previous reports, and patients with HFpEF were older and more often female.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Patients with HFpEF are older, more often female, and more frequently have hypertension compared to patients with HFrEF [2,11,12,[16][17][18][19][20][21]. Similar background differences were demonstrated in Japanese HF patients in both inpatient-based and community-based cohorts [3,4]. The differences in patients' backgrounds in our study were almost identical to those of previous reports, and patients with HFpEF were older and more often female.…”
Section: Discussionsupporting
confidence: 83%
“…The epidemiology of HF in Japan is different from that in Western countries with respect to ethnic background and etiology. However, there are few Japanese hospital-based reports about preserved left ventricular ejection fraction (LVEF) [2][3][4], and the prevalence and prognosis of HF with preserved LVEF are not well known. Tsuchihashi-Makaya et al examined patients from the Japanese Cardiac Registry of Heart Failure in Cardiology who were hospitalized for HF and demonstrated that patients with HFpEF had similar mortality rates and equally high rates of rehospitalization as those with HFrEF [4].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of diabetes and atrial fibrillation are thought to be similar between preserved and reduced LVEF. According to recent reports from Japan, similar background differences could be applied to Japanese HF patients in both inpatient-based and community-based cohorts [18,19]. Actually, the differences in patient's backgrounds in our study were almost identical to those of previous reports, in that patients with preserved LVEF tended to be older and were more likely to be women.…”
Section: Patient Backgroundssupporting
confidence: 75%
“…The epidemiology of HF in Japan should be quite different from that in Western countries in respect of ethnic background and etiology. However, there are few Japanese hospital-based reports about preserved LVEF [8,18,19], and the prevalence and prognosis of HF with preserved LVEF are not well known. The purpose of the present study was to determine the prevalence, prognosis, and predictors for mortality of HF patients in both inpatients and outpatients, with preserved versus reduced LVEF in a prospective cohort fashion.…”
Section: Introductionmentioning
confidence: 99%
“…• Cardiac dysfunction (CD) -clinical manifestations of heart failure (Killip classes II to IV) and/or laboratory tests showing the presence of left ventricular systolic dysfunction (LVSD) during hospitalization 21,22 : echocardiography within the first 72 hours of hospital admission showing moderate or severe global systolic dysfunction associated with ejection fraction ≤ 40% using the Teichholz method 23 , or ejection fraction ≤ 40% using the Simpson method, or invasive contrast ventriculography during coronary angiography showing moderate or severe systolic dysfunction 24 .…”
Section: Definition Of Variablesmentioning
confidence: 99%